International capital flows and development: Financial openness matters - Dennis Reinhardt; Luca Antonio Ricci; Thierry Tressel (Graduate Institute of International and Development Studies, 2012)
Does capital flow from rich to poor countries? We revisit the Lucas paradox and explore the role of capital account restrictions in shaping capital flows at various stages of economic development. We find that, when accounting for the degree of capital account openness, the prediction of the neoclassical theory is confirmed: less developed countries tend to experience net capital inflows and more developed countries tend to experience net capital outflows, conditional on various countries' characteristics.
Keywords: F21; F36; O4; 330; Lucas paradox; capital flows; financial openness; economic development; Kapitalexport; Industriestaaten-seitig; Kapitalmobilität; Finanzmarktregulierung; Wirtschaftswachstum; Entwicklungsländer; Welt